Krider-Mallogh-Dana double wedding, Santa Maria - McMillan Bros::::::photographer::: (1890)
Written on back: 'May 21, 1890, John O. Krider and Mollie Dana (John Dana), Wm. Mallagh and Nellie Dana (Carlos Dana). Wedding written up in The Daily Republic of SLO - Thurs. May 22, 1890. May 21, 1890 - John P. Krider (of Santa Maria) + Miss Mollie Dana of Nipomo (John F. Dana). William Mallagh + Miss Nellie Dana of SLO (Carlos W. Dana). The brides were cousins.'